Corrosion-resistant polyolefin composite pipe and preparation method thereof

By coating the inner wall of the composite tube with corrosion-resistant coating composed of polytetrafluoroethylene resin and modified nano-silica, a superhydrophobic coating is formed, which solves the corrosion problems caused by chemicals and microorganisms in wastewater and extends the service life of the composite tube.

CN119713007APending Publication Date: 2025-03-28JIANGSU NOBEL PLASTICS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411951315.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Sewage contains chemical substances and microorganisms such as acids, alkalis, salts, etc., which causes corrosion of plastic pipes and reduces service life.

Method used

The corrosion-resistant coating is used to coat the inner wall of the composite tube. The coating consists of polytetrafluoroethylene resin, silane modified nanosilica and unmodified nanosilica to form a superhydrophobic coating to prevent sewage from adhesion and corrosion.

Benefits of technology

It effectively reduces the corrosion risk of composite pipes, extends service life, and improves corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119713007A_ABST
    Figure CN119713007A_ABST
Patent Text Reader

Abstract

The invention relates to a corrosion-resistant polyolefin composite pipe and a preparation method thereof, and relates to the technical field of composite pipes. The composite pipe comprises a composite pipe body, the inner wall of the composite pipe body is coated with a corrosion-resistant layer, the corrosion-resistant layer is obtained by coating the inner wall of the composite pipe body with corrosion-resistant paint, and the corrosion-resistant paint is prepared from, by mass, 55-60 parts of polytetrafluoroethylene resin, 15-19 parts of filler, 0.5-0.9 part of polyamide and 22-28 parts of ethyl acetate. The filler comprises silane modified nano silicon dioxide and unmodified nano silicon dioxide; the silane modified nano silicon dioxide comprises KH-570 modified nano silicon dioxide and KH-550 modified nano silicon dioxide; the composite pipe has the effects of improving the corrosion resistance of the composite pipe and prolonging the service life of the composite pipe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite pipes, and in particular to a corrosion-resistant polyolefin composite pipe and a preparation method thereof. Background Art

[0002] Plastic pipes have the advantages of light weight, high strength, simple manufacturing method, low economic cost, convenient processing and use, etc., and gradually replace metal, cement and other pipes, becoming the main application pipes in urban construction, rural water network laying, industrial liquid material transmission and other fields. Sewage treatment is the process of purifying sewage to meet the water quality requirements for discharge into a certain water body or reuse. Sewage treatment is widely used in various fields such as construction, agriculture, transportation, energy, petrochemical, environmental protection, urban landscape, medical treatment, catering, etc., and is increasingly entering the daily life of ordinary people. In recent years, the number of sewage treatment plants has increased rapidly.

[0003] However, since sewage contains chemical substances such as acid, alkali, salt and microorganisms, when sewage flows through plastic pipes, the chemical substances will react chemically with the plastic pipe materials, and the microorganisms will grow and multiply on the inner wall of the pipe to form a biofilm, thereby causing corrosion of the plastic pipe and reducing the service life of the plastic pipe. Summary of the invention

[0004] In order to improve the corrosion resistance of the composite pipe and extend the service life of the composite pipe, the present application provides a corrosion-resistant polyolefin composite pipe and a preparation method thereof.

[0005] In the first aspect, the present application provides a corrosion-resistant polyolefin composite pipe, which adopts the following technical solution: A corrosion-resistant polyolefin composite pipe, comprising a composite pipe body, the inner wall of which is coated with a corrosion-resistant layer, wherein the corrosion-resistant layer is obtained by coating a corrosion-resistant coating on the inner wall of the composite pipe body, wherein the corrosion-resistant coating comprises the following raw materials in parts by weight: 55-60 parts of polytetrafluoroethylene resin, 15-19 parts of filler, 0.5-0.9 parts of polyamide, and 22-28 parts of ethyl acetate; The filler includes silane-modified nano-silicon dioxide and unmodified nano-silicon dioxide; The silane-modified nano-silica includes KH-570-modified nano-silica and KH-550-modified nano-silica.

[0006] By adopting the above technical scheme, KH-570 and KH-550 modify nano silicon dioxide, reducing the phenomenon that nano silicon dioxide agglomerates too seriously. It is generally believed that unmodified silicon dioxide is not conducive to dispersion, and the present application creatively selects different silane-modified silicon dioxide and unmodified silicon dioxide to mix, and can form micro-agglomerates with different degrees of dispersion, and also promotes the uniform dispersion of unmodified nano silicon dioxide to a certain extent, and then the filler and polytetrafluoroethylene resin of different dispersibility formed by different silane-modified nano silicon dioxide and unmodified nano silicon dioxide can construct a rough structure of micro-nano level, and the surface energy of nano silicon dioxide modified by KH-570 and KH-550 is low, so that the coating formed after polytetrafluoroethylene resin is mixed with filler can form super-hydrophobic coating on the inner wall of composite pipe body, and then sewage will be discharged when it appears near super-hydrophobic coating, and then it is difficult to adhere to or even close to the surface layer of composite pipe body, reducing the possibility of corrosion of composite pipe and extending the service life of composite pipe.

[0007] Preferably, the method for preparing the silane-modified nano-silicon dioxide comprises the following steps: S100, adding nano-silicon dioxide to a mixed solution of anhydrous ethanol and deionized water, stirring evenly, then adding KH-570, stirring fully, then heating in a water bath, then centrifuging, washing, and drying to obtain KH-570 modified nano-silicon dioxide; adding nano-silicon dioxide to a mixed solution of anhydrous ethanol and deionized water, stirring evenly, then adding KH-550, stirring fully, then heating in a water bath, then centrifuging, washing, and drying to obtain KH-550 modified nano-silicon dioxide; S200, mixing KH-570 modified nano-silica and KH-550 modified nano-silica, stirring evenly, and preparing silane modified nano-silica.

[0008] By adopting the above technical solution, the hydroxyl groups on the surface of nano-silica react with the hydroxyl groups produced after the hydrolysis of KH-570 and KH-550, thereby grafting and modifying the nano-silica to obtain organic hydrophobic modified nano-silica, which effectively improves the hydrophobicity of the nano-silica.

[0009] Preferably, the mass ratio of nano-silica to KH-570 in the KH-570 modified nano-silica is 1:(0.15-0.25), and the mass ratio of nano-silica to KH-550 in the KH-550 modified nano-silica is 1:(0.20-0.26).

[0010] By adopting the above technical solution, the mass ratio of KH-570 modified nano-silica and KH-550 modified nano-silica in the preparation process is controlled within the above range, which effectively improves the hydrophobicity of the nano-silica.

[0011] Preferably, the filler further comprises modified nano zinc oxide, and the mass ratio of the silane-modified nano silicon dioxide to the modified zinc oxide is 1:(1.5-1.7); The modified nano zinc oxide comprises nano zinc oxide and stearic acid.

[0012] By adopting the above technical scheme, the nano zinc oxide modified with stearic acid not only improves the solubility of nano zinc oxide in organic solvents, but also forms a lamellar structure. The lamellar structure is filled with silane-modified nano silica particles to form an intercalated composite structure, which can disperse the coating stress generated after the partial agglomeration of the modified nano particles, thereby inhibiting the generation of coating pores, ensuring that the coating micro-nano structure brings higher hydrophobicity while maintaining the continuous durability of the coating. At the same time, the organic-inorganic hybrid network formed by the nanoparticles and the polytetrafluoroethylene resin improves the binding force of the coating, and the fillers of different particle sizes increase the packing density of the nano fillers in the coating, thereby minimizing the pores of the coating, improving the overall corrosion resistance of the super hydrophobic coating, and further extending the service life of the composite pipe.

[0013] Preferably, the preparation method of the modified nano zinc oxide comprises the following steps: Add nano zinc oxide and stearic acid into anhydrous ethanol, stir evenly, and then centrifuge and dry in sequence to obtain modified nano zinc oxide.

[0014] By adopting the above technical solution, nano zinc oxide forms a more obvious and continuous lamellar structure after being modified by stearic acid. At the same time, the carboxyl group of stearic acid condenses with the hydroxyl group of nano zinc oxide, reducing the number of hydroxyl groups on the surface of nano zinc oxide particles and improving the hydrophobicity of nano zinc oxide.

[0015] Preferably, the mass ratio of the nano zinc oxide to stearic acid is 1:(0.22-0.32).

[0016] By adopting the above technical solution, the mass ratio of nano zinc oxide and stearic acid is controlled within the above range, which can effectively improve the hydrophobicity of nano zinc oxide.

[0017] Preferably, the corrosion-resistant coating further comprises 5-7 parts of carbon nanotubes.

[0018] By adopting the above technical solution, the interaction between the carbon nanotubes and the layered modified nano zinc oxide and the silane modified nano silicon dioxide improves the corrosion resistance of the composite tube.

[0019] The addition of carbon nanotubes can significantly improve the density of the coating, form a physical barrier, and effectively isolate the contact between the corrosive medium and the composite tube, thereby slowing down the corrosion process.

[0020] Preferably, the carbon nanotubes are prepared by modification, and the modification preparation method of the carbon nanotubes comprises the following steps: Hexadecyltrimethylammonium bromide is added into deionized water, stirred evenly, then carbon nanotubes are added, stirred sufficiently, centrifuged and dried in sequence to obtain modified carbon nanotubes.

[0021] By adopting the above technical solution, the carbon nanotubes are treated with hexadecyltrimethylammonium bromide, so that the hexadecyltrimethylammonium bromide is adsorbed on the surface of the carbon nanotubes, thereby improving the dispersibility of the carbon nanotubes.

[0022] Preferably, the mass ratio of the carbon nanotubes to hexadecyltrimethylammonium bromide is 1:(0.2-0.4).

[0023] By adopting the above technical solution, the mass ratio of carbon nanotubes to hexadecyltrimethylammonium bromide is controlled within the above range, which can effectively improve the dispersibility of the carbon nanotubes.

[0024] In a second aspect, the present application provides a method for preparing a corrosion-resistant polyolefin composite pipe as in the first aspect, which adopts the following technical solution: S1. Mix the filler and ethyl acetate, stir them thoroughly, add polytetrafluoroethylene resin and polyamide, stir them evenly, and let them stand to obtain a corrosion-resistant coating; S2. Apply the corrosion-resistant coating to the surface of the composite pipe body, and after curing, obtain a corrosion-resistant polyolefin composite pipe.

[0025] In summary, the present application includes at least one of the following beneficial technical effects: KH-570 and KH-550 modify the nano-silica, reduce the phenomenon of excessive agglomeration of nano-silica, form tiny agglomerates with different degrees of dispersion, promote the uniform dispersion of unmodified nano-silica, and then through the action of fillers formed by different silane-modified nano-silica and unmodified nano-silica and polytetrafluoroethylene resin, a micro-nanoscale rough structure can be constructed. The surface energy of the nano-silica modified by KH-570 and KH-550 is low, so the coating formed by mixing polytetrafluoroethylene resin and filler can form a super-hydrophobic coating on the inner wall of the composite pipe body, and then when sewage appears near the super-hydrophobic coating, it will be discharged, making it difficult to adhere to or even approach the surface of the composite pipe body, reducing the possibility of corrosion of the composite pipe and extending the service life of the composite pipe.

[0026] The stearic acid-modified nano zinc oxide not only improves the solubility of nano zinc oxide in organic solvents, but also forms a lamellar structure. The lamellar structure is filled with silane-modified nano silica particles to form an intercalated composite structure, which can disperse the coating stress generated after the modified nano particles agglomerate, thereby inhibiting the generation of coating pores. At the same time, the organic-inorganic hybrid network formed by the nanoparticles and the polytetrafluoroethylene resin improves the binding force of the coating, and the fillers of different particle sizes increase the packing density of the nanofillers in the coating, thereby minimizing the pores of the coating, improving the overall corrosion resistance of the super hydrophobic coating, and further extending the service life of the composite pipe. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the overall structure of a corrosion-resistant polyolefin composite pipe in an embodiment of the present application.

[0028] Description of reference numerals: 1. Composite pipe body; 2. Corrosion-resistant layer. DETAILED DESCRIPTION

[0029] The following is combined with Figure 1 This application is described in further detail.

[0030] The present application embodiment discloses a corrosion-resistant polyolefin composite pipe. Figure 1 , comprising a composite pipe body 1, the inner wall of the composite pipe body 1 is coated with a corrosion-resistant coating 2, and the corrosion-resistant coating 2 is obtained by coating the corrosion-resistant coating on the inner wall of the composite pipe body 1.

[0031] The present application is further described in detail below in conjunction with the embodiments and comparative examples. The raw materials involved in the present application can be obtained commercially, among which polytetrafluoroethylene resin (CAS No.: 9002-84-0) is provided by Shanghai Haohong Biotechnology Co., Ltd., and polyamide (CAS No.: 63428-84-2) is provided by Shanghai MacLean Biochemical Technology Co., Ltd. Example

[0032] The corrosion-resistant coating includes the following components by weight: 55 g of polytetrafluoroethylene resin, 15 g of filler, 0.5 g of polyamide, and 22 g of ethyl acetate.

[0033] The preparation method of silane-modified nano-silicon dioxide comprises the following steps: S100, 3g of nano-silicon dioxide was added to a mixed solution of 50g of anhydrous ethanol and 10g of deionized water, and ultrasonically dispersed for 15min, then 0.45g of KH-570 was added, and ultrasonically dispersed for 10min, and then placed in a 70°C water bath and stirred for 6h at a speed of 350r / min. After cooling to 25°C, the mixture was centrifuged in a centrifuge (the speed of the centrifuge was 8000r / min), the supernatant was poured out, and then the unreacted KH-570 was removed by centrifugal washing with anhydrous ethanol, and finally dried in a vacuum oven at 100°C for 12h to obtain KH-570 modified nano-silicon dioxide. Silica; 3g of nano-silica was added to a mixed solution of 50g of anhydrous ethanol and 10g of deionized water, and then 0.60g of KH-550 was added after ultrasonic dispersion for 15min, and then placed in a 70°C water bath and stirred for 6h at a speed of 350r / min, and then cooled to 25°C and centrifuged using a centrifuge (the speed of the centrifuge was 8000r / min), the supernatant was poured out, and then the unreacted KH-550 was removed by centrifugal washing with anhydrous ethanol, and finally dried in a vacuum oven at 100°C for 12h to obtain KH-550 modified nano-silica; S200, mixing KH-570 modified nano-silica and KH-550 modified nano-silica, stirring evenly, and preparing silane modified nano-silica.

[0034] The mass ratio of KH-570 modified nano-silica to KH-550 modified nano-silica is 1:0.9.

[0035] The filler includes silane-modified nano-silica and unmodified nano-silica, and the mass ratio of the silane-modified nano-silica to the unmodified nano-silica is 1:0.2.

[0036] The preparation method of the filler comprises the following steps: The silane-modified nano-silicon dioxide and the unmodified nano-silicon dioxide are mixed and stirred evenly to obtain a filler.

[0037] The method for preparing a corrosion-resistant polyolefin composite pipe comprises the following steps: S1. After mixing the filler and ethyl acetate, stir at a speed of 500 / min for 15 min, then add polytetrafluoroethylene resin and polyamide, stir at a speed of 1000 / min for 30 min, and then stand for 30 min to prepare a corrosion-resistant coating; S2. Apply the corrosion-resistant coating to the surface of the composite pipe body and dry it at 20° C. for 24 hours to obtain a corrosion-resistant polyolefin composite pipe. Example

[0038] The corrosion-resistant coating includes the following components by weight: 60 g of polytetrafluoroethylene resin, 19 g of filler, 0.9 g of polyamide, and 28 g of ethyl acetate.

[0039] The preparation method of silane-modified nano-silicon dioxide comprises the following steps: S100, 3g of nano-silicon dioxide was added to a mixed solution of 50g of anhydrous ethanol and 10g of deionized water, and ultrasonically dispersed for 15min, then 0.75g of KH-570 was added, and ultrasonically dispersed for 10min, and then placed in a 70°C water bath and stirred for 6h at a speed of 350r / min. After cooling to 25°C, the mixture was centrifuged in a centrifuge (the speed of the centrifuge was 8000r / min), the supernatant was poured out, and then the unreacted KH-570 was removed by centrifugal washing with anhydrous ethanol, and finally dried in a vacuum oven at 100°C for 12h to obtain KH-570 modified nano-silicon dioxide. Silica; 3g of nano-silica was added to a mixed solution of 50g of anhydrous ethanol and 10g of deionized water, and then 0.72g of KH-550 was added after ultrasonic dispersion for 15min, and then placed in a 70°C water bath and stirred for 6h at a speed of 350r / min, and then cooled to 25°C and centrifuged using a centrifuge (the speed of the centrifuge was 8000r / min), the supernatant was poured out, and then the unreacted KH-550 was removed by centrifugal washing with anhydrous ethanol, and finally dried in a vacuum oven at 100°C for 12h to obtain KH-550 modified nano-silica; S200, mixing KH-570 modified nano-silicon dioxide and KH-550 modified nano-silicon dioxide, stirring evenly, and preparing modified nano-silicon dioxide.

[0040] The mass ratio of KH-570 modified nano-silica to KH-550 modified nano-silica is 1:0.9.

[0041] The filler includes silane-modified nano-silica and unmodified nano-silica, and the mass ratio of the silane-modified nano-silica to the unmodified nano-silica is 1:0.2.

[0042] The preparation method of the filler comprises the following steps: The silane-modified nano-silicon dioxide and the unmodified nano-silicon dioxide are mixed and stirred evenly to obtain a filler.

[0043] The method for preparing a corrosion-resistant polyolefin composite pipe comprises the following steps: S1. After mixing the filler and ethyl acetate, stir at a speed of 500 / min for 15 min, then add polytetrafluoroethylene resin and polyamide, stir at a speed of 1000 / min for 30 min, and then stand for 30 min to prepare a corrosion-resistant coating; S2. Apply the corrosion-resistant coating to the surface of the composite pipe body and dry it at 20° C. for 24 hours to obtain a corrosion-resistant polyolefin composite pipe. Example

[0044] The corrosion-resistant coating includes the following components by weight: 58 g of polytetrafluoroethylene resin, 17 g of filler, 0.7 g of polyamide, and 25 g of ethyl acetate.

[0045] The preparation method of silane-modified nano-silicon dioxide comprises the following steps: S100, 3g of nano-silicon dioxide was added to a mixed solution of 50g of anhydrous ethanol and 10g of deionized water, and ultrasonically dispersed for 15min, then 0.60g of KH-570 was added, and ultrasonically dispersed for 10min, and then placed in a 70°C water bath and stirred for 6h at a speed of 350r / min. After cooling to 25°C, the mixture was centrifuged in a centrifuge (the speed of the centrifuge was 8000r / min), the supernatant was poured out, and then the unreacted KH-570 was removed by centrifugation and washing with anhydrous ethanol. Finally, the mixture was dried in a vacuum oven at 100°C for 12h to obtain KH-570 modified nano-silicon dioxide. Silica; 3g of nano-silica was added to a mixed solution of 50g of anhydrous ethanol and 10g of deionized water, and then 0.69g of KH-550 was added after ultrasonic dispersion for 15min, and then placed in a 70°C water bath and stirred for 6h at a speed of 350r / min, and then cooled to 25°C and centrifuged using a centrifuge (the speed of the centrifuge was 8000r / min), the supernatant was poured out, and then the unreacted KH-550 was removed by centrifugal washing with anhydrous ethanol, and finally dried in a vacuum oven at 100°C for 12h to obtain KH-550 modified nano-silica; S200, mixing KH-570 modified nano-silica and KH-550 modified nano-silica, stirring evenly, and preparing silane modified nano-silica.

[0046] The mass ratio of KH-570 modified nano-silica to KH-550 modified nano-silica is 1:0.9.

[0047] The filler includes silane-modified nano-silica and unmodified nano-silica, and the mass ratio of the silane-modified nano-silica to the unmodified nano-silica is 1:0.2.

[0048] The preparation method of the filler comprises the following steps: The modified nano silicon dioxide and the unmodified nano silicon dioxide are mixed and stirred evenly to obtain a filler.

[0049] The method for preparing a corrosion-resistant polyolefin composite pipe comprises the following steps: S1. After mixing the filler and ethyl acetate, stir at a speed of 500 / min for 15 min, then add polytetrafluoroethylene resin and polyamide, stir at a speed of 1000 / min for 30 min, and then stand for 30 min to prepare a corrosion-resistant coating; S2. Apply the corrosion-resistant coating to the surface of the composite pipe body and dry it at 20° C. for 24 hours to obtain a corrosion-resistant polyolefin composite pipe. Example

[0050] The difference between Example 4 and Example 3 is that the mass ratio of nano-silica to KH-570 in KH-570-modified nano-silica is 1:0.05; the mass ratio of nano-silica to KH-550 in KH-550-modified nano-silica is 1:0.10. Example

[0051] The difference between Example 5 and Example 3 is that the mass ratio of nano-silica to KH-570 in KH-570-modified nano-silica is 1:0.36; the mass ratio of nano-silica to KH-550 in KH-550-modified nano-silica is 1:0.36. Example

[0052] The difference between Example 6 and Example 3 is that the filler further contains modified nano zinc oxide, and the mass ratio of silane-modified nano silicon dioxide to modified nano zinc oxide is 1:1.5.

[0053] The preparation method of modified nano zinc oxide comprises the following steps: 10 g of nano zinc oxide and 2.2 g of stearic acid were added to 50 g of anhydrous ethanol, and the mixture was ultrasonically stirred for 30 min, and then the supernatant was removed using a centrifuge. The mixture was then dried at 50° C. for 12 h to obtain modified nano zinc oxide.

[0054] The preparation method of the filler comprises the following steps: The filler is prepared by mixing the silane-modified nano silicon dioxide and the modified nano zinc oxide. Example

[0055] The difference between Example 7 and Example 3 is that the filler further contains modified nano zinc oxide, and the mass ratio of silane-modified nano silicon dioxide to modified nano zinc oxide is 1:1.7.

[0056] The preparation method of modified nano zinc oxide comprises the following steps: 10 g of nano zinc oxide and 3.2 g of stearic acid were added to 50 g of anhydrous ethanol, and the mixture was ultrasonically stirred for 30 min, and then the supernatant was removed using a centrifuge. The mixture was then dried at 50° C. for 12 h to obtain modified nano zinc oxide.

[0057] The preparation method of the filler comprises the following steps: The filler is prepared by mixing the silane-modified nano silicon dioxide and the modified nano zinc oxide. Example

[0058] The difference between Example 8 and Example 3 is that the filler further contains modified nano zinc oxide, and the mass ratio of silane-modified nano silicon dioxide to modified nano zinc oxide is 1:1.6.

[0059] The preparation method of modified nano zinc oxide comprises the following steps: 10 g of nano zinc oxide and 2.7 g of stearic acid were added to 50 g of anhydrous ethanol, and the mixture was ultrasonically stirred for 30 min, and then the supernatant was removed using a centrifuge. The mixture was then dried at 50° C. for 12 h to obtain modified nano zinc oxide.

[0060] The preparation method of the filler comprises the following steps: The filler is prepared by mixing the silane-modified nano silicon dioxide and the modified nano zinc oxide. Example

[0061] The difference between Example 9 and Example 8 is that the mass ratio of silane-modified nano-silicon dioxide to modified nano-zinc oxide is 1:1.3. Example

[0062] The difference between Example 10 and Example 8 is that the mass ratio of silane-modified nano-silicon dioxide to modified nano-zinc oxide is 1:1.9. Example

[0063] The difference between Example 11 and Example 8 is that the mass ratio of nano zinc oxide to stearic acid is 1:0.12. Example

[0064] The difference between Example 12 and Example 8 is that the mass ratio of nano zinc oxide to stearic acid is 1:0.42. Example

[0065] The difference between Example 13 and Example 8 is that the corrosion-resistant coating further includes 5g of carbon nanotubes.

[0066] The method for preparing a corrosion-resistant polyolefin composite pipe comprises the following steps: S1. After mixing the filler and ethyl acetate, stirring at a speed of 500 / min for 15 min, adding polytetrafluoroethylene resin, polyamide and carbon nanotubes, stirring at a speed of 1000 / min for 30 min, and then standing for 30 min to prepare a corrosion-resistant coating; S2. Apply the corrosion-resistant coating to the surface of the composite pipe body and dry it at 20° C. for 24 hours to obtain a corrosion-resistant polyolefin composite pipe. Example

[0067] The difference between Example 14 and Example 13 is that the corrosion-resistant coating further includes 7g of carbon nanotubes. Example

[0068] The difference between Example 15 and Example 13 is that the corrosion-resistant coating further includes 6 g of carbon nanotubes. Example

[0069] The difference between Example 16 and Example 15 is that the carbon nanotubes are prepared by modification, and the modification preparation method of the carbon nanotubes comprises the following steps: 0.2 g of hexadecyltrimethylammonium bromide was added to 1000 g of deionized water, stirred at 200 r / min for 3 min using a constant temperature magnetic stirrer, and then 1 g of carbon nanotubes was added. The mixture was ultrasonicated at 20 kHz for 240 min using an ultrasonic generator. After standing at 25°C for 24 h, the mixture was centrifuged and dried in sequence to obtain modified carbon nanotubes. Example

[0070] The difference between Example 17 and Example 15 is that the carbon nanotubes are prepared by modification, and the modification preparation method of the carbon nanotubes comprises the following steps: 0.4 g of hexadecyltrimethylammonium bromide was added to 1000 g of deionized water, stirred at 200 r / min for 3 min using a constant temperature magnetic stirrer, and then 1 g of carbon nanotubes was added. The mixture was ultrasonicated at 20 kHz for 240 min using an ultrasonic generator. After standing at 25°C for 24 h, the mixture was centrifuged and dried in sequence to obtain modified carbon nanotubes. Example

[0071] The difference between Example 18 and Example 15 is that the carbon nanotubes are prepared by modification, and the modification preparation method of the carbon nanotubes comprises the following steps: 0.3 g of hexadecyltrimethylammonium bromide was added to 1000 g of deionized water, stirred at 200 r / min for 3 min using a constant temperature magnetic stirrer, and then 1 g of carbon nanotubes was added. The mixture was ultrasonicated at 20 kHz for 240 min using an ultrasonic generator. After standing at 25°C for 24 h, the mixture was centrifuged and dried in sequence to obtain modified carbon nanotubes. Example

[0072] The difference between Example 19 and Example 18 is that the mass ratio of carbon nanotubes to hexadecyltrimethylammonium bromide is 1:0.1. Example

[0073] The difference between Example 20 and Example 18 is that the mass ratio of carbon nanotubes to hexadecyltrimethylammonium bromide is 1:0.5.

[0074] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the filler is unmodified nano-silicon dioxide.

[0075] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the filler is silane-modified nano-silica.

[0076] Performance testing: The composite tubes prepared in Examples 1-20 and Comparative Examples 1-2 were tested.

[0077] Corrosion resistance: The breakage pressure is tested according to the standard CB / T4138-2011, and the absolute value of the breakage pressure change rate is tested after 80wt% sulfuric acid and 3mol / L sodium hydroxide solution flow in the composite pipe for 24 hours.

[0078]

[0079] Data analysis Specifically combined with the test results of Example 8 and Example 3, the absolute value of the breakage pressure change rate of Example 8 after the circulation of sulfuric acid and sodium hydroxide solution for 24 hours is less than that of Example 3. The analysis is as follows: the difference between Example 8 and Example 3 is that stearic acid modifies the nano zinc oxide, so that a more obvious and continuous lamellar structure is formed, and the hydrophobicity of the nano zinc oxide is improved, so that the lamellar structure is filled with silane-modified nano silicon dioxide particles to form an intercalated composite structure, which can disperse the coating stress generated after the modified nano particles are agglomerated, thereby inhibiting the generation of coating pores, ensuring that the coating micro-nano structure brings higher hydrophobicity while maintaining the continuous durability of the coating. At the same time, the organic-inorganic hybrid network formed by the nanoparticles and the polytetrafluoroethylene resin improves the binding force of the coating, thereby improving the corrosion resistance of the corrosion-resistant coating, and effectively improving the corrosion resistance of the composite pipe.

[0080] Specifically combining the test results of Example 15 and Example 8, the absolute value of the change rate of the damage pressure of Example 15 after the circulation of sulfuric acid and sodium hydroxide solution for 24 hours is smaller than that of Example 8. The analysis is as follows. The difference between Example 15 and Example 8 is that the addition of carbon nanotubes can significantly improve the density of the composite material, and the interaction between the carbon nanotubes and the layered modified nano zinc oxide and silane modified nano silicon dioxide improves the corrosion resistance of the corrosion-resistant coating, thereby improving the corrosion resistance of the composite pipe.

[0081] Specifically combining the test results of Example 18 and Example 15, the absolute value of the change rate of the damage pressure of Example 18 after the circulation of sulfuric acid and sodium hydroxide solution for 24 hours is smaller than that of Example 15. The analysis is as follows: the difference between Example 18 and Example 15 is that the carbon nanotubes are treated with hexadecyltrimethylammonium bromide to improve the dispersion of the carbon nanotubes, thereby improving the positive effect of the carbon nanotubes on improving the corrosion resistance of the corrosion-resistant coating, thereby improving the corrosion resistance of the composite pipe.

[0082] Specifically combining the test results of Example 3 and Comparative Example 1, the absolute value of the breakage pressure change rate of Example 3 after the circulation of sulfuric acid and sodium hydroxide solution for 24 hours is smaller than that of Comparative Example 1. The analysis is as follows: the difference between Example 3 and Comparative Example 1 is that the silane-modified nano-silica can form tiny agglomerates with different degrees of dispersion, which promotes the uniform dispersion of the unmodified nano-silica, and then a micro-nanoscale rough structure can be constructed through the action of the silane-modified nano-silica, the unmodified nano-silica and the polytetrafluoroethylene resin, thereby forming a super-hydrophobic coating, thereby improving the corrosion resistance of the composite pipe.

[0083] Specifically combining the test results of Example 3 and Comparative Example 2, the absolute value of the breakage pressure change rate of Example 3 after the circulation of sulfuric acid and sodium hydroxide solution for 24 hours is smaller than that of Comparative Example 1. The analysis is as follows: the difference between Example 3 and Comparative Example 1 is that the silane-modified nano-silica can form tiny agglomerates with different degrees of dispersion, which promotes the uniform dispersion of the unmodified nano-silica, and then the micro-nanoscale rough structure can be constructed through the action of the silane-modified nano-silica and the polytetrafluoroethylene resin, thereby forming a super-hydrophobic coating, thereby improving the corrosion resistance of the composite pipe.

[0084] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A corrosion-resistant polyolefin composite pipe, characterized in that: The composite pipe body (1) comprises a composite pipe body (1), the inner wall of which is coated with a corrosion-resistant layer (2), the corrosion-resistant layer (2) being obtained by coating a corrosion-resistant coating on the inner wall of the composite pipe body (1), the corrosion-resistant coating comprising the following raw materials in parts by weight: 55-60 parts of polytetrafluoroethylene resin, 15-19 parts of filler, 0.5-0.9 parts of polyamide, and 22-28 parts of ethyl acetate; The filler includes silane-modified nano-silicon dioxide and unmodified nano-silicon dioxide; The silane-modified nano-silica includes KH-570-modified nano-silica and KH-550-modified nano-silica.

2. The corrosion-resistant polyolefin composite pipe according to claim 1, characterized in that: The preparation method of the silane-modified nano-silicon dioxide comprises the following steps: S100, adding nano-silicon dioxide to a mixed solution of anhydrous ethanol and deionized water, stirring evenly, then adding KH-570, stirring fully, then heating in a water bath, then centrifuging, washing, and drying to obtain KH-570 modified nano-silicon dioxide; adding nano-silicon dioxide to a mixed solution of anhydrous ethanol and deionized water, stirring evenly, then adding KH-550, stirring fully, then heating in a water bath, then centrifuging, washing, and drying to obtain KH-550 modified nano-silicon dioxide; S200, mixing KH-570 modified nano-silica and KH-550 modified nano-silica, stirring evenly, and preparing silane modified nano-silica.

3. The corrosion-resistant polyolefin composite pipe according to claim 2, characterized in that: The mass ratio of nano-silicon dioxide to KH-570 in the KH-570 modified nano-silicon dioxide is 1:(0.15-0.25), and the mass ratio of nano-silicon dioxide to KH-550 in the KH-550 modified nano-silicon dioxide is 1:(0.20-0.26).

4. The corrosion-resistant polyolefin composite pipe according to claim 2, characterized in that: The filler also includes modified nano zinc oxide, and the mass ratio of the silane-modified nano silicon dioxide to the modified nano zinc oxide is 1:(1.5-1.7); The modified nano zinc oxide comprises nano zinc oxide and stearic acid.

5. The corrosion-resistant polyolefin composite pipe according to claim 4, characterized in that: The preparation method of the modified nano zinc oxide comprises the following steps: Add nano zinc oxide and stearic acid into anhydrous ethanol, stir evenly, and then centrifuge and dry in sequence to obtain modified nano zinc oxide.

6. The corrosion-resistant polyolefin composite pipe according to claim 4, characterized in that: The mass ratio of the nano zinc oxide to stearic acid is 1:(0.22-0.32).

7. The corrosion-resistant polyolefin composite pipe according to claim 4, characterized in that: The corrosion-resistant coating also includes 5-7 parts of carbon nanotubes.

8. The corrosion-resistant polyolefin composite pipe according to claim 7, characterized in that: The carbon nanotubes are prepared by modification, and the modification preparation method of the carbon nanotubes comprises the following steps: Hexadecyltrimethylammonium bromide is added into deionized water, stirred evenly, then carbon nanotubes are added, stirred sufficiently, centrifuged and dried in sequence to obtain modified carbon nanotubes.

9. The corrosion-resistant polyolefin composite pipe according to claim 8, characterized in that: The mass ratio of the carbon nanotubes to hexadecyltrimethylammonium bromide is 1:(0.2-0.4).

10. A method for preparing a corrosion-resistant polyolefin composite pipe according to claim 1, characterized in that: The steps include: S1. Mix the filler and ethyl acetate, stir them thoroughly, add polytetrafluoroethylene resin and polyamide, stir them evenly, and let them stand to obtain a corrosion-resistant coating; S2. Apply the corrosion-resistant coating to the surface of the composite pipe body, and after curing, obtain a corrosion-resistant polyolefin composite pipe.

Citation Information

Patent Citations

  • Vegetable oil based polyurethane / silicon dioxide nano composite material and preparation method thereof

    CN104327236A

  • Weather-proof oil-proof high-adhesiveness coating for ships

    CN105694645A

  • Coating with excellent antifouling performance

    CN108997857A

  • Quaternary ammonium salt modified carbon nanotube, preparation method thereof, low-density and low-warpage soft-touch polypropylene modified material and preparation method thereof

    CN110615914A

  • Pipeline protective coating and production process thereof

    CN115044275A